The left temporal pole is a convergence region mediating the relation between names and semantic knowledge for unique entities: Further evidence from a "recognition-from-name" study in neurological patients. (December 2018) - Schneider, Brett; Heskje, Jonah; Bruss, Joel; Tranel, Daniel; Belfi, Amy M.
Abstract: Prior research has implicated the left temporal pole (LTP) as a critical region for naming semantically unique items, including famous faces, landmarks, and musical melodies. Most studies have used a confrontation naming paradigm, where a participant is presented with a stimulus and asked to retrieve its name. We have proposed previously that the LTP functions as a two-way, bidirectional convergence region brokering between conceptual knowledge and proper names for unique entities. Under this hypothesis, damage to the LTP should result in a "two way" impairment: (1) defective proper name retrieval when presented with a unique stimulus (as shown in prior work); and (2) defective concept retrieval when presented with a proper name. Here, we directly tested the second prediction using a "recognition-from-name" paradigm. Participants were patients with LTP damage, brain-damaged comparisons with damage outside the LTP, and healthy comparisons. Participants were presented with names of famous persons (e.g., "Marilyn Monroe"), landmarks (e.g., "Leaning Tower of Pisa"), or melodies (e.g., "Rudolph the Red-Nosed Reindeer") and were asked to provide conceptual knowledge about each. We found that individuals with damage to the LTP were significantly impaired at conceptual knowledge retrieval when given names of famous people and landmarks (but this finding did not hold for melodies). This outcome supports the theory that the LTP is a bidirectional convergence region for proper naming, but suggests that melody retrieval may rely on processes different from those supported by the LTP.